(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The connecting rod is an intermediate element between the piston and the crankshaft. Its main function is to transmit thrust and ejection from the piston pin onto the crank pin, so as to convert the reciprocating motion of the piston into the crank rotating motion. This study includes FEA analysis and experimental modal analysis of a cane. A parametric model of the connecting rod is modelled using the CATIA V5 R19 software, and the finite element analysis is performed using the ANSYS software. The finite element method is used to determine the natural frequency of a cane and comparing the results with the FFT analyser. FFT analysis is performed by hanging the connecting rod at the toeing foot, and the experimental results are compared with FEM.